EVALUATION OF THE PRESENCE OF RISK FACTORS FOR FOOT ULCERATION IN PATIENTS WITH TYPE, 2 DIABETES MELLITUS - Serpil Savaş,; Meltem Çetin,; H. Rifat Koyuncuoğlu,; Ş. Ercan Tunç, (Archives of Rheumatology, 2001)
The main risk factors for diabetic foot ulcers are peripheral sensory neuropathy with foot deformities and limited joint mobility. The aim of this study is to evaluate the risk factors for foot ulceration among the patients with type 2 diabetes mellitus. Thirty-seven patients and 30 sex and age matched controls were included in the study. Ankle and subtalar joint passive range of motion was measured in patients and controls for the presence of limited joint mobility. Standardized dorsoplantar and lateral weight-bearing radiographs of both feet of each participant were taken. Calcaneal inclination angle was used as an index of the height of the foot framework. Hallux valgus deformity was determined by the measurement of abduction of the hallux. Electroneuromyography (EMG) was performed for the diagnosis of the peripheral neuropathy. There were no difference in the ankle and subtalar joint passive range of motion between the patients and controls (p>0,05). Peripheral neuropathy was the most commonly detected risk factor in our patients and also a high number of hallux valgus and/or pes planus deformities were detected. The patients who have peripheral neuropathy and these deformities were accepted as having high risk for the development of foot ulcers. Education and wearing suitable shoes may prevent these patients from the diabetic ulcers.